Education on pain disciplines in physical therapy in Chile: In need of change - Órdenes-Mora, José Alfredo [UNESP]; Almeida-Terassi, Laiza Moura; Wartemberg, Manuel Ahumada; Reis, Felipe J. J. (Medwave Estudios Limitada, 2023)
Pain is a major public health concern associated with emotional disorders and physical disability and generates increased sick leave and healthcare expenditures. However, despite its social impact and the high pain-related costs, the training of healthcare professionals, such as physical therapists, in pain management is insufficient, leading to an inadequate therapeutic approach. This study aimed to determine the existence of a specific program on pain within the curricula of physical therapy careers in accredited universities in Chile. Out of 40 physical therapy careers, we analyzed 38 curricula. None of them had a specific discipline on pain management in their curricula. Although there is no concrete definition of the best modality for pain education in undergraduate students, it has been shown that following the International Association for The Study of Pain curricula improves students' knowledge and awareness of pain management.
Educación sobre las disciplinas del dolor en las carreras de kinesiología en Chile: necesidad de un cambio
Keywords: education; Pain; Physical therapy